1998
DOI: 10.2527/1998.764937x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the interval from weaning to estrus in first-litter sows: correlated responses.

Abstract: ABSTRACT:The objective of this study was to evaluate relationships between rebreeding performance and growth performance ( n = 3,777 gilts) and rebreeding performance and reproductive performance ( n = 2,242 sows). Our data were from a selection experiment for shorter intervals from weaning to estrus after the first parity (IWE), involving Dutch Landrace pigs, in which a selection line and a control line without selection were maintained for eight generations. Relationships were evaluated before and after tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…Selection for decreased A100 will also favorably decrease the interval from weaning to first service. This is contrary to results of ten Johnson (1997) andten Napel et al (1998), which suggested that selection for increased daily gain and reduced BF would increase the probability of a long WTS interval. They found no correlation to the interval from weaning to first service treated as a continuous trait, and they also questioned the accuracy of using WTS on a continuous scale.…”
Section: Discussioncontrasting
confidence: 98%
“…Selection for decreased A100 will also favorably decrease the interval from weaning to first service. This is contrary to results of ten Johnson (1997) andten Napel et al (1998), which suggested that selection for increased daily gain and reduced BF would increase the probability of a long WTS interval. They found no correlation to the interval from weaning to first service treated as a continuous trait, and they also questioned the accuracy of using WTS on a continuous scale.…”
Section: Discussioncontrasting
confidence: 98%
“…Estimates between these traits reported by ten Napel et al (1998) were close to zero, −0.09 and 0.08, respectively. The genetic correlation between BC and PREGNANT was positive but with large PSD (r g = 0.18, PSD = 0.27).…”
Section: Correlationsmentioning
confidence: 59%
“…same population at 0.14 (Lundgren et al, 2012). In a study by ten Napel et al (1998), body condition at weaning was measured by trained technicians using a similar scale as in the present study. The heritability was estimated at 0.33.…”
Section: Heritabilitiesmentioning
confidence: 97%
“…In adjusting litter size for previous WCI, we are assuming that the effect is mainly environmental. The genetic correlation between WCI and litter size is reported to be small (Adamec and Johnson, 1997;Ten Napel et al, 1998). If WCI has an important genetic correlation with litter size, then the correct procedure would be to use a multivariate model to produce EBV for both litter size and WCI.…”
Section: Resultsmentioning
confidence: 99%